2011
DOI: 10.1111/j.1464-5491.2011.03251.x
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of patients from quality measurement of diabetes care in the UK pay‐for‐performance programme

Abstract: Patients excluded from pay-for-performance programmes may be less likely to achieve treatment goals and disproportionately come from disadvantaged groups. Permitting physicians to exclude patients from pay-for-performance programmes may worsen health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 24 publications
(25 reference statements)
4
47
0
Order By: Relevance
“…We identified 15 retrospective cohort studies 30,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] and three cross sectional surveys 15,46,47 related to the inner setting. Studies of the QOF found that larger practices in the UK performed better in the short term, [33][34][35] particularly when examining total QOF points; 37 however, results varied when examining subgroups by condition or location and by indicator.…”
Section: Inner Setting (18 Studies)mentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 15 retrospective cohort studies 30,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] and three cross sectional surveys 15,46,47 related to the inner setting. Studies of the QOF found that larger practices in the UK performed better in the short term, [33][34][35] particularly when examining total QOF points; 37 however, results varied when examining subgroups by condition or location and by indicator.…”
Section: Inner Setting (18 Studies)mentioning
confidence: 99%
“…Inner setting Eighteen studies 15,30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] examined implementation factors related to the inner setting. Studies found:…”
Section: Implementation Processesmentioning
confidence: 99%
“…Appropriate and permissible exception reporting, however, should exclusively be determined by patient characteristics. Dalton et al (2011) discover significantly higher rates of exception reporting for already disadvantaged patient groups such as older patients and ethnic minorities. In consequence, P4P could lead to greater health disparities since exception reported patients are less likely to achieve treatment targets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors find that non-profit providers of substance abuse treatment in the U.S. treat less severely ill patients and avoid more severe cases in order to improve overall performance. Gravelle et al (2010) and Dalton et al (2011) report gaming of exception reporting under the QOF. Exception reporting is an instrument that allows the exclusion of patients from certain QOF quality indicators based on broad clinical criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These metrics were adopted from reasonably vetted measures from sources such as the National Quality Forum. Unfortunately, in ESRD, multiple well researched quality measures based on hard outcomes are lacking, such that the measures included in the QIP do not have strong evidence supporting a beneficial effect on important patient outcomes (Table 3) (22)(23)(24)(25)(26)(27)(28).…”
Section: Legislative Pay For Performance: Acos and The Esrd Qipmentioning
confidence: 99%